2019
DOI: 10.5435/jaaos-d-19-00424
|View full text |Cite
|
Sign up to set email alerts
|

A Focused Gap Year Program in Orthopaedic Research: An 18-Year Experience

Abstract: Introduction: Students seek gap years to enhance knowledge and improve chances of professional success. Although many institutions offer research opportunities, no studies have examined outcomes after these experiences. This study evaluates a dedicated year of orthopaedic research on a cohort's ultimate orthopaedic surgery match rate. Methods: From 2001 to 2018, 129 learners spent a year with our Department of Orthopedic Surgery at a major academic medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…Sidiqi et al 18 noted in a 2016 survey of applicants for Radiology-Oncology, another competitive subspecialty, 68% of students stated that the primary purpose of their research gap year was to obtain more publications. The suggestion that students who participated in a research year do so to improve their application parallels the findings of Egol et al 11 who found that gap-year students have slightly lower USMLE step 1 scores (236 versus 240) and USMLE step 2 scores (243 versus 247). The belief in the importance of a research year, however, did not entirely align with those of the 72 program directors surveyed with only 3 (4.2%) agreeing that a research year was an important factor for residency selection.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Sidiqi et al 18 noted in a 2016 survey of applicants for Radiology-Oncology, another competitive subspecialty, 68% of students stated that the primary purpose of their research gap year was to obtain more publications. The suggestion that students who participated in a research year do so to improve their application parallels the findings of Egol et al 11 who found that gap-year students have slightly lower USMLE step 1 scores (236 versus 240) and USMLE step 2 scores (243 versus 247). The belief in the importance of a research year, however, did not entirely align with those of the 72 program directors surveyed with only 3 (4.2%) agreeing that a research year was an important factor for residency selection.…”
Section: Discussionsupporting
confidence: 71%
“… 1 , 2 This has led to an increase in the number of medical students participating in nondegree research years; however, the value of these research years and their effect on research productivity during residency remained unknown. 2 , 11 Our study found that residents who had completed a research year during medical school produced more peer-reviewed journal publications during residency than their peers who had not. However, this may be due to a variety of factors, including greater familiarity and experience with research gained during the year, self-selection bias with residents who were more interested in research electing to partake in a research year, and/or established relationships with research mentors if they conducted their research year at their ultimate residency institution.…”
Section: Discussionmentioning
confidence: 63%
“…To date, the sole orthopaedic study investigating how RGY might affect match success was a review of a single, large academic institution's 18-year experience with offering RGY opportunities. Egol et al 2 noted a higher match rate in these students compared with NRMP published data. The authors surveyed 129 students who spent a full-year within the Department of Orthopedic Surgery at their center after college graduation, during or after medical school, or after an unsuccessful first match attempt into orthopaedics.…”
Section: Discussionmentioning
confidence: 61%
“…The number of applicants applying to orthopaedic surgery residency programs continues to increase annually. 1 - 3 Several applicant characteristics have been correlated with greater match success, including higher US Medical Licensing Examination (USMLE) step 1 scores, 4 - 6 admission into the Alpha Omega Alpha (AOA) honor society, 5 , 6 and having a greater mean number of applicant self-reported research activities in matched applicants (4.6 vs 3.0 from applicant data 2007 to 2014). 5 USMLE Step 1 will become pass/fail in 2022, leading to speculation on what applicant factors will increase in importance as a result.…”
mentioning
confidence: 99%
See 1 more Smart Citation